Origins, ancestry and alliance : explorations in Austronesian ethnography - Sather, Clifford; Fox, James J., 1940- (Occasional paper of the Department of Anthropology, Research School of Pacific Studies, the Australian National University., 2006)
"This collection of papers, the third in a series of volumes on the work of the Comparative Austronesian Project, explores indigenous Austronesian ideas of origin, ancestry and alliance and considers the comparative significance of these ideas in social practice. The papers examine social practice in a diverse range of societies extending from insular Southeast Asia to the islands of the Pacific."--Publisher's description